Integrin Linked Kinase (ILK) and its Role in Liver Pathobiology - Martucci, Nicole (Gene Expr, 2021)
Integrin linked kinase (ILK) is a vital signaling protein ubiquitously expressed throughout the body. It binds to intracellular integrins to help promote signaling related to cell adhesion, apoptosis, proliferation, migration, and a plethora of other common cellular functions. In this review, ILK’s role in the liver is detailed. Studies have shown ILK to be a major participant in hepatic ECM organization, liver regeneration, insulin resistance, and hepatocellular carcinoma.